PERANCANGAN SISTEM INFORMASI MEMBERSHIP PADA PT INDITAMA BERBASIS WEBSITE - Nur Azizah; Rini Tisnawati (INFOKOM (Informatika & Komputer), 2023)
This study aimed to design and build implementation information system membership at PT. Inditama website-based. From the research carried out there are several problems, namely: (1) The tracking process history client not effective and efficient, (2) The data storage process is operated using Microsoft excel, very old data searches, and an optimum ungenerated report made, (3) There is no membership dashboard. Therefore, the writer makes the design oriented method with the UML as design diagram, PHP as programming language, MySQL as database. The research method used a qualitative method with a descriptive approach. The techniques of collecting data used method observation, interview, and litelature study. Software development method used is Waterfall method. There are suggestion, such as: application can be developed in terms of security which still considered lacking, some features that are not optimal can still be developed to be more responsive, this application can be developed until the design stage is more interactive so that it can be interconnected with other information systems.